Antioxidant and antiglycation activities and inhibitory action of Passiflora cincinnata on collagenase, elastase and tyrosinase: in vitro and in silico study. (September 2022) - da Costa Gomes, Amanda; Figueiredo, Célia Cristina Malaguti; Granero, Filipe Oliveira; Junior, João Luiz Bronzel; Ximenes, Valdecir Farias; Silva, Luciana Pereira; Nicolau-Junior, Nilson; da Silva, Regildo Márcio Gonçalves
Abstract: Passiflora species are widely used in folk medicine due to their sedative and anxiolytic activities; however, scientific studies also showed different biological activities (antioxidant, anti-inflammatory, antidiabetic and antimicrobial). The present study aimed to characterize the phytochemical profile of P. cincinnata hydroethanolic extract, evaluate its antioxidant and antiglycation activities and evaluate in silico molecular docking of its main flavonoids. Phytochemical characterization was performed by quantification of total polyphenols and flavonoids content, and High Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) analysis. Antioxidant activity was determined by 2, 2-Diphenyl-1-picrylhydrazyl (DPPH), Ferric reducing antioxidant power (FRAP), Nitric oxide (NO) and Thiobarbituric acid reactive species (TBARS) tests. Antiglycation activity was determined by Relative Electrophoretic Mobility (REM) and free amino groups assays. P. cincinnata presented total polyphenols (62 mg gallic acid equivalent (GAE) g −1 dry weight (DW)) and flavonoids (57 mg rutin equivalent (RE) g −1 DW), besides HPLC-MS showed the presence of different flavonoids glucoside, mainly vitexin and orientin. The extract presented antioxidant activity by DPPH (76.60%), FRAP (276.70 μM trolox equivalent (TE) g −1 DW), TBARS (80.30% inhibition) and NO (10.10 μM mL −1 nitrite formed). REM demonstrated that extract presents antiglycation activity similar to Bovine serum albumin treated with Aminoguanidine; additionally, it showed 22% free amino groups. In silico assay demonstrated that orientin exhibited the highest interaction with DNA and the best docking score with elastase and collagenase. Therefore, the present study showed the protective properties of P. cincinnata hydroethanolic extract against oxidative stress and glycation. It also showed the presence of polyphenols and flavonoids, and their interaction with DNA and enzymes. Highlights: Passiflora species are widely used due to their diverse medicinal effects. Vitexin and Orientin were the main flavonoid found in P. cincinnata extract. P. cincinnata aerial parts extract presented antioxidant and antiglycation activities. P. cincinnata presented inhibitory action on collagenase, elastase and tyrosinase. Orientin the most likely ligand for DNA and best docking score for enzymes.